The Role of Fine-needle Aspiration Cytology in Guiding Clinicians for Lymphadenopathy - Saurabh Kumar; Sampa Choudhury; Vineeta Chadha; Suparna Dubey; Mhasisielie Zumu (Journal of Surgical Specialties and Rural Practice, 2024)
Background: Lymphadenopathy is a very common, routinely observed clinical finding which may be caused by a variety of pathological conditions, either a primary lymph node pathology or an underlying systemic disease. Fine-needle aspiration is a simple cost-effective diagnostic tool to screen these lesions, to enhance our knowledge, to understand lymph node pathology, as well as to assist clinicians for an effective management.